Pengetahuan Perawat Tentang Penanganan Restrain Dalam Kegawatdaruratan Psikiatri : Deskriptif Kuantitatif Survey - Wildan Akasyah; Winanda rizki bagus santosa (Nursing Sciences Journal, 2024)
Background: Mental health crisis is a major issue for ODGJ and can endanger others and the environment. In handling psychiatric emergencies, the expertise of nurses is very important and needed. In the process, nurses have personal traits or qualities that can influence knowledge. Objective: The purpose of this study was to find the effect of age and education on the knowledge of health center nurses on how to handle patients with psychiatric emergencies. Methods: Using a sample of 91 respondents selected by cluster sampling technique. The research method used a cross-sectional approach. Demographic survey and knowledge assessment test (The Phisical Restraint Questionare) on how to handle psychiatric emergencies in patients were used to collect data. Results: Ordinal logistic regression analysis of the model fitting data provided results in the form of an association between the variables of age and education with knowledge and the degree of nurse expertise as indicated by a decrease in the value of -2 log Like hood decreased from 73.99 (Intercept Only) to 61.52 (Final) with p=0.029 (<0.05). Conclusion: The variables show that the model fits the data, meaning that the variables of age and education level together affect the level of knowledge of nurses about handling restraints in psychiatric emergency patients. Suggestion: Training programs for nurses on physical restraints need to be carried out continuously so that the quality of care provided by nurses when physically restraining psychiatric patients is getting better.   Keywords: Knowledge, Restraint, Psychiatric Emergency